2019
DOI: 10.1155/2019/8748253
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial Role of Phytochemicals on Oxidative Stress and Age-Related Diseases

Abstract: Aging is related to a number of functional and morphological changes leading to progressive decline of the biological functions of an organism. Reactive Oxygen Species (ROS), released by several endogenous and exogenous processes, may cause important oxidative damage to DNA, proteins, and lipids, leading to important cellular dysfunctions. The imbalance between ROS production and antioxidant defenses brings to oxidative stress conditions and, related to accumulation of ROS, aging-associated diseases. The purpo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
240
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 364 publications
(247 citation statements)
references
References 167 publications
(159 reference statements)
4
240
0
3
Order By: Relevance
“…Increasing the total phenolic is an advantage for human health, where those phytochemicals possess many biologically significant functions, such as protection against oxidative stress, and degenerative diseases (Forni et al, 2019). Another interesting finding of this research is the insignificant effect of N and micronutrients application on the phenolic compounds in cauliflower curds.…”
Section: Discussionmentioning
confidence: 75%
“…Increasing the total phenolic is an advantage for human health, where those phytochemicals possess many biologically significant functions, such as protection against oxidative stress, and degenerative diseases (Forni et al, 2019). Another interesting finding of this research is the insignificant effect of N and micronutrients application on the phenolic compounds in cauliflower curds.…”
Section: Discussionmentioning
confidence: 75%
“…Moreover, its effect on other carcinogens depends on a number of factors including, the carcinogen, target organ, exposure parameters, as well as the animal being tested. The toxicity of butylated hydroxytoluene is suggested to be the result of it being an electrophilic metabolite [38][39][40][41][42][43] . Numerous www.nature.com/scientificreports www.nature.com/scientificreports/ studies have revealed that Butylated hydroxyl toluene "BHT" acts as a potent antioxidant that significantly inhibits cytokine-induced inflammatory responses in both human and mouse cells 44 .…”
Section: Discussionmentioning
confidence: 99%
“…Vitamin C is produced in the process of oxygen metabolism and quickly reacts with singlet oxygen, ozone, and H 2 O 2 in the process of ascorbic peroxidase, which allows it to neutralize their toxic effects. In plants, vitamin C also contributes to the regeneration of other strong antioxidants: carotenoids and vitamin E [167]. Vitamin C is capable of crossing the blood-brain barrier and trapping free radicals both intra-and extracellularly.…”
Section: Vitamins and Provitaminsmentioning
confidence: 99%
“…The antioxidative activity of carotenoids stems from their ability to trap peroxide radicals. The number of conjugated double bonds in these molecules corresponds to their effectiveness in trapping ROS [167]. Astaxanthin (3,30-dihydroxy-β, β-carotene-4,40-dione) is a red pigment belonging to the sub-class of xanthophyllic carotenoids; it is found mainly in microalgae, mushrooms, and complex plants, as well as in salmon, trout, and crustacean cells [114].…”
Section: Vitamins and Provitaminsmentioning
confidence: 99%